Analisis Pola Penataan Massa pada Pondok Pesantren Bertaraf Internasional - Dima Hifdhia; Umi Farhah; Erwin Djuni (Jurnal Talenta Sipil, 2023)
With globalization, the world has grown so that it has an impact on various aspects of education. Religious education is one of the most important character education and is mandatory for every Muslim. With the development of advanced international Islamic boarding schools, aspects of education, especially character, will not be affected by changes in globalization and times. The pattern of behavior of a student has a close relationship with the response to the arrangement of the mass of the boarding school building. The arrangement of the mass of the building is very important, a good and appropriate arrangement of the mass of the building will lead to a good pattern of behavior as well. What is a good arrangement of building masses at an International Islamic Boarding School? This research method uses qualitative, observation and in-depth study of several case studies, so that it will produce a mass arrangement that is in accordance with the activity patterns of international Islamic boarding school students.